CAUCASIAN TANDEM AND THE BELT AND ROAD INITIATIVE - ISMAILOV, Eldar; PAPAVA, Vladimer (CENTRAL ASIA AND THE CAUCASUS, 2018)
The paper discusses the issues of the joint role of Azerbaijan and Georgia, or the “Caucasian Tandem,” in Beijing’s Belt and Road Initiative global project. Proceeding from the Caucasian Tandem’s experience in establishing and operating the Silk Road Transport Corridor, the chief challenges of the Silk Road Economic Belt implementation are examined. In the context of the Russian geopolitical theory of Eurasianism and the historical experience of overcoming the Moscow-driven challenges in establishing the Silk Road Transport Corridor, the article analyzes potential hindrances in implementing the segment of the Silk Road Economic Belt that should traverse the Central Caucasus. Special emphasis is placed on the Russian project of the Greater Eurasian Partnership or Community, as a more broad-scale reinterpretation of the Eurasian Economic Union, which Moscow considers an alternative to Beijing’s Belt and Road Initiative project. A comparison of the major characteristics of Russia’s and China’s economic models allowed to determine that the Eurasian Economic Union, and all the more so the Greater Eurasian Partnership or Community, is unable to compete with the Belt and Road Initiative, although it can create certain geopolitical obstacles to its implementation. The paper substantiates that in order to increase the efficiency of functioning of the Central Caucasian segment of the Silk Road Economic Belt, it is essential to transit from the alternative economic corridor paradigm (which is of a confrontational nature) to a paradigm of their mutual complementarity (which is of a healthy competitive nature). The mutual complementarity paradigm aims to harmonize the development of the corridors under consideration. Such an approach to economic corridors was once proposed to weaken the confrontational character of the transport and energy corridors traversing Russia and the Central Caucasus. The Caucasian Tandem successfully plays the role of a transport and energy hub in the Silk Belt transport corridor system. The Belt and Road Initiative creates a potential opportunity for the transformation of this transport and energy hub into a more complex economic hub. It is in this context that the paper emphasizes the special role of Georgia, which will hold the primary burden in the creation of the trade and economic hub, since it is already involved in free trade relations with China, the European Union, and the European Free Trade Association. In order for these trading models to be utilized, the goods exported from Georgia to these regions have to be manufactured in Georgia, which increases its investment attractiveness. Joint operation of the economic hub being created and the already functioning transport and energy hub in the Central Caucasus will establish great prospects for the Caucasian Tandem’s economic development.